On holographic thermalization and gravitational collapse of massless scalar fields - Wu, Bin (The journal of high energy physics, 2012)
A bstract In this paper we study thermalization in a strongly coupled system via AdS/CFT. Initially, the energy is injected into the system by turning on a spatially homogenous scalar source coupled to a marginal composite operator. The thermalization process is studied by numerically solving Einstein’s equations coupled to a massless scalar field in the Poincare patch of AdS 5 . We define a thermalization time t T on the AdS side, which has an interpretation in terms of a spacelike Wilson loop in CFT. Here T is the thermal equilibrium temperature. We study both cases with the source turned on in short and long durations. In the former case, the thermalization time and the coefficient in the limit . In the latter case, we find double- and multiple-collapse solutions, which may be interpreted as the gravity duals of two- or multi-stage thermalization in CFT. In all the cases our results indicate that such a strongly coupled system thermalizes in a typical time scale .